Access and use of weather and climate information by women and men farmers: Rwanda Climate Services for Agriculture qualitative evaluation preliminary findings - Gumucio, Tatiana; Hansen, James; Rose, Alison (2019)
The Rwanda Climate Services for Agriculture project has sought to build capacity of the country’s national institutions to provide climate information tailored to the needs of the agriculture sector, deliver climate services to farmers across Rwanda’s 30 districts, and help them to effectively use the information to manage climate risk. Project interventions include: training Farmer Promoters, who are part of Rwanda’s national agricultural extension service, to guide farmers in the Participatory Integrated Climate Services for Agriculture (PICSA) process (Dorward et al., 2015); and organizing farmers into Radio Listeners’ Clubs that meet weekly to participate in climate services radio programs and discuss management responses.